Sub-state nationalism and populism: the cases of Vlaams Belang, New Flemish Alliance and DéFI in Belgium. Issue 6 (November 2018) - Haute, Emilie; Pauwels, Teun; Sinardet, Dave
Abstract This contribution assesses whether populism is inherently embedded in and combined with the ideology of sub-state nationalist parties, using Belgium as a case study. We argue that sub-state nationalist parties tend to emphasize the opposition between a territorial community ('us') versus a dominant center ('them'), a dichotomous view that could overlap with the populist ideology focusing on the opposition between the homogeneous people and the 'corrupt' elite. We compare the policy positions of the three major sub-state nationalist parties that operate in Belgium: the Vlaams Belang, the New Flemish Alliance (N-VA) and Democrat Federalist Independent, using their manifestos and membership magazines between 2010 and 2015. We show that the manner in which sub-state nationalist parties combine their stances on territoriality to a populist rationale depends on their relationship to power (government vs. opposition). In doing so, this contribution uniquely relates populism to the territorial dimension of Belgian politics.